Foreign fighters in Ukraine : the brown-red cocktail - Rekawek, Kacper (Routledge studies in facism and the far right, 2023)
Foreign Fighters in Ukraine is the first comprehensive academic study taking an in-depth look at foreigners who have chosen to fight in the conflict in Ukraine. While there has been considerable focus in policy, security and academic circles on the threat from returning jihadists - so-called returnee foreign terrorist fighters - the same danger from right-wing, but not essentially terrorist, extremists and others has been largely overlooked. As Westerners rushed to join the nascent Caliphate in Syria/Iraq, others simultaneously traveled to another foreign war on what many would call Europe's doorstep: the Russo-Ukrainian war. This book unmasks this largely unknown group of fighters as the author dives into the fighters' ideological and social backgrounds, their motivations for joining the conflict, their travails on the way there and their battle record in Eastern Ukraine. To a large extent based on interviews with the fighters themselves, it is a study on how and why men risk their lives while fighting a foreign war - and attract the attention of security services at home upon their return. Particularly, given the Russian invasion of Ukraine in February 2022 and the growing interest in far-right violence worldwide, the book evaluates whether these returnees constitute another security threat to the West.